Design and Implementation of On-Line Practice System Based on Software Testing. Issue 1 (January 2021) - Jiang, Weiyi; Deng, Junyu
Abstract: As an important branch of software testing, software automated testing has brought many conveniences to the B/S architecture of Web application software testing. At the same time, it has also put forward new requirements for talents in the field of software testing. It is necessary to understand the theoretical knowledge of software testing and to master the use of software testing tools. Therefore, colleges and universities must adopt a teaching model that combines theory with practice to train more excellent test talents. The online practice system adopts the B/S architecture mode, integrates Spring, SpringMVC, and MyBatis open-source frameworks for system development, realizes the function module of super administrator management background, and supports student users to practice theoretical exercises related to software testing online, and write Web-compliant Selenium test script for applying test questions. The system can refer to the Selenium test script according to the standard and compare the test script submitted by the student user. The Selenium tags, positioning methods, elements, and attribute values are regarded as important scoring objects, and finally, judge and make reasonable scoring feedback.